Conceiving Migration and Communication in a Global Perspective - Aliu, Armando (Cambridge Scholars Publisher, 2020)
Migration and communication are issues of major concern in today's world. This volume examines diversified approaches to migration and communication, and explores policy dialogues, migration governance, transnationalism, cross-border circular migration and many other viewpoints of importance today. It sheds lights on recent debates in Europe associated with cross-national perspectives, socio-economic challenges, welfare rights and social cohesion, multi-scalar applications and policy-driven migration. The text synthesises various complex arguments and recent debates in migration and translatio.